PENGGUNAAN MEDIA SOSIAL SEBAGAI TRIGGER ADVOKASI KEBIJAKAN PROGRAM KIP-K DI UNIVERSITAS DIPONEGORO TAHUN 2024 - Afdi Bintang Syabana; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Public discussion about alleged mistargeting of the Kartu Indonesia Pintar Kuliah (KIP-K) program at Universitas Diponegoro in 2024 went viral on social media and Triggered a surge of digital advocacy. This study analyzes social media as a Policy-advocacy Trigger and explains coalition negotiation within the Policy Subsystem using the Advocacy Coalition Framework (ACF). Employing a qualitative descriptive-analytic design, the study draws on in-depth interviews with university bureaucratic actors and student organizations, complemented by documentation of social media content and relevant internal documents. Findings reveal two dominant coalitions: an institutional coalition emphasizing procedural legitimacy and privacy protection, and a transparency–distributive coalition emphasizing targeting fairness, transparency, and accountability. Social media acts as a strategic resource for issue framing, public opinion mobilization, and Pressure Politics that accelerate institutional responses. A Policy Broker role emerges through mediation mechanisms and communication channels that reduce conflict escalation and foster Policy-oriented learning. Coalition interaction produces Policy Outputs such as reactivating an official complaint channel, strengthening routine recipient evaluation (including an additional personal-income indicator), and initiating plans for field verification (offline surveys). Nevertheless, social-media advocacy also carries risks of doxxing, cyberbullying, and social stigmatization, calling for stronger digital ethics and clearer mediation governance.